2018
DOI: 10.1111/bju.14605
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of penile curvature: a population‐based cross‐sectional study in metropolitan and rural cities in Australia

Abstract: ObjectiveTo evaluate the prevalence of penile curvature and healthseeking behaviour in Australian men. ConclusionsThis first population-based study to estimate the prevalence of penile curvature in Australia highlighted that penile curvature is common and has a significant adverse impact on psychosexual functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…In the Koln prevalence study performed in 8,000 males, PD prevalence, proven with the presence of palpable plaque, was reported to be 3.2%. 14 In another population-based prevalence study carried out online in Australia, 1,782 male participants answered questions and PD prevalence was found to be 19.9% 18 The risk of PD increases with advancing age and in this study, the median age of PD patients was 52 years. In the prevalence study carried out by Sommer et al, PD most frequently occurred in the age group between 50 and 59 years.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In the Koln prevalence study performed in 8,000 males, PD prevalence, proven with the presence of palpable plaque, was reported to be 3.2%. 14 In another population-based prevalence study carried out online in Australia, 1,782 male participants answered questions and PD prevalence was found to be 19.9% 18 The risk of PD increases with advancing age and in this study, the median age of PD patients was 52 years. In the prevalence study carried out by Sommer et al, PD most frequently occurred in the age group between 50 and 59 years.…”
Section: Discussionmentioning
confidence: 50%
“…The exact prevalence of PD may be challenging to estimate because males may either exaggerate or hide complaints about their sexuality. 18 In studies of prevalence, disparities in age, geographical regions, socioeconomic situations, and assessment of co-existing diseases may cause a variance in PD prevalence. 24 Also, because populations are assessed in various milieus (groups, hospitals, etc), different results might emerge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peyronie's disease (PD) is a relatively common psychosexual condition characterized by the presence of penile pain, curvature and/or deformity, palpable plaque(s) and erectile dysfunction (ED) [1]. The published literature shows a strong association between PD and psychological issues such as depression, low self-esteem and altered relationship dynamics, with adverse impact on masculinity, sexual confidence and satisfaction [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Large population epidemiological studies report a discordance between the physician's and patient-reported perceptions; the rates of PD vary among different countries and across various institutions, highlighting that these differences may be related to different social views on self-reporting, the varying methodology used for clinical detection, as well as the diversity of sexual practices and perceived sexual dysfunction among men with PD. A recent national study conducted through a third party in Australia showed that at least one in 10 men reported a bend or curve in the penis [3]. Furthermore, the incidence of PD appears to be higher in men with cardiovascular and metabolic conditions such as diabetes and hypogonadism [4], while the presence of fibrotic disorders such as Dupuytren's contracture is more common in men with PD, especially among the older population [5].…”
Section: Introductionmentioning
confidence: 99%